Development of Pneumonia Risk Early Detection Instruments in Puskesmas Area, Semarang City - Tolang, Korsini Heru Setiawan; Isnaeni, Wiwi; Masrukan, Masrukan (Journal of Research and Educational Research Evaluation, 2018)
This research was motivated by the absence of an early detection instrument for the risk of pneumonia that was tested for validity and reliability. Instruments about pneumonia found in integrated management of sick toddlers have less detailed indicators that only include breathing speed. The aim of the study was to produce an instrument of early detection of the risk of pneumonia that was valid and reliable. This research is a development research conducted in the Puskesmas ngemplak in Semarang. The subject of this study was 100 respondents. Test the content validity using Aiken's V formula and reliability test using Hoyt. In the trial, the reliability was analyzed using Alpha Cronbach. In the validity and reliability test the valid instrument items were more than 0.3 for each item and the instrument reliability was at 0.869> 0.7. The construct validity test using Confirmatory Factor Analysis (CFA) formed 3 factors, namely factor 1 (signs and symptoms), factor 2 (individual behavior) and factor 3 (environment). This study produces valid and reliable instruments. The benefit of this study is that instruments that are valid and reliable can be used as a standard guide in knowing how much a person is exposed to pneumonia